The Inevitable Challenge of Ethical Dilemmas in Optometry, Part 1: When Confidentiality is Tested - Faucher, Caroline; Rezk, Marina; Verni, Ariana (Canadian Journal of Optometry, 2022)
Healthcare professionals often face ethical dilemmas, which arise when two ethical principles conflict. Despite the potential for psychological consequences, no study has examined ethical dilemmas in the field of optometry. Objective. This article is the first in a series of three pertaining to a joint study that aimed to identify and describe the ethical dilemmas faced by optometrists. Method. An online survey sent to 1,393 optometrists asked them about various categories of ethical dilemmas. Unlimited space was provided for explanations. Results. Each of the 22 ethical dilemmas proposed had previously been encountered by between 3.75% and 67.9% of the 240 respondents. This first article reports that ethical dilemmas involving confidentiality are varied and those pertaining to the filling out of driver’s licence forms had previously affected 40% of the participants. Conclusion. Optometrists regularly face tough ethical decisions for which knowledge of the legislation and regulations alone is insufficient. The results will be revealed in the next two articles in this series, with the last one broaching the discussion of how to optimize the management of ethical issues in the field of optometry.